Выражение: 1) (m-2)² - (m+1)(m-3) 2) 5(d - c)² + 10dc 3) x в третьей степени +(2-х)(х²- 2х+4) решите )

вероника1046 вероника1046    2   25.06.2019 16:20    0

Ответы
tisha199567 tisha199567  20.07.2020 18:45
(m-2)² - (m+1)(m-3)=m²-2m+4-m²+3m-m+3=m+7
5(d - c)² + 10dc=5(d²-2dc+c²)+10dc=5d²-10+5c²+10dc=5d²+5c²
ПОКАЗАТЬ ОТВЕТЫ
ангел150705 ангел150705  20.07.2020 18:45
1) =m^2-4m+4-(m^2-3m+m-3)=-2m+7
2) =5(d^2-2dc+c^2)+10dc=5d^2+5c^2
3) =x^3+2x^2-4x+8-x^3+2x^2-4x=4x^2-8x+8
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра